The Exfoliation of Crystalline Covalent Triazine Frameworks by Glycerol Intercalation. Issue 12 (24th May 2021) - Liu, Jing; Liu, Manying; Wang, Xueqing; Wang, Kewei; Jin, Shangbin; Tan, Bien
Abstract: It is a huge challenge to exfoliate covalent triazine frameworks (CTFs) into large‐area CTF sheets, because of the ultrastrong triazine linkage and its high crystallinity. Herein, a glycerol intercalation strategy is reported to exfoliate bulk crystalline CTF‐HC1 into large‐area crystalline E‐CTF‐HC1 sheets. The three vibration states of glycerol molecules at 25, 90, and 300 °C are a key role in the process of CTFs exfoliation. As the temperature increases, the vibration energy increases. When the temperature reaches 300 °C, the vibration energy becomes large enough to make the glycerol occupy the CTF layer spacing at the vibrational state of the maximum cross section, resulting in the exfoliation of CTFs. The specific capacitance of the exfoliated E‐CTF‐HC1 electrode (342.15 F g −1 at 0.1 A g −1 ) is about 3.3 times higher than that of bulk CTF‐HC1 electrode (104.04 F g −1 at 0.1 A g −1 ). Abstract : A novel glycerol intercalation strategy is shown to efficiently fabricate large‐area crystalline covalent triazine frameworks (CTF) sheets. With the assist of glycerol molecules' random vibration, the highly crystalline CTF‐HCl is successfully exfoliated into large‐area crystalline E‐CTF‐HC1 sheets. The exfoliated E‐CTF‐HC1 exhibits higher specific surface area, higher ionic conductivity, higher specific capacitance (342.15 F g −1 at 0.1 A g −1 ) when used as electrode materials.